Fluorescent probes for the detection of cyanide ions in aqueous medium: cellular uptake and assay for beta-glucosidase and hydroxynitrile lyase - Agarwalla, Hridesh; Gangopadhyay, Monalisa; Sharma, Dharmendar Kumar; Basu, Santanu Kumar; Jadhav, Sameer; Chowdhury, Arindam; Das, Amitava (Journal of Materials Chemistry B, 2015)
A chemodosimteric reagent (1) for the efficient detection of cyanide species (CN- and/or HCN) in aq. medium as well as under physiological conditions has been described. Selective reaction of the cyanide species with this reagent in the presence of all common interfering anions, amino acids and glutathione (GSH) led to the generation of the corresponding cyanohydrin derivative. The formation of the cyanohydrin derivative of the probe is associated with a visually detectable change in solution fluorescence in aq. buffer medium with 1.9 mu M NaCN, the threshold limit set by WHO for the safe drinking water and this makes this fluorogenic sensor an ideal candidate for in-field applications. An apparent switch on the luminescence response, ultralow detection limit, low response time, cell membrane permeability and insignificant toxicity are key features of a probe molecule, which gives it a distinct edge over previously reported chemodosimetric reagents for the detection of cyanide species (CN- or HCN) in an aqueous environment. This methodology could be used for developing a generalized and efficient fluorescence-based assay for crucial enzymes like beta-glucosidase and hydroxynitrile lyase. Furthermore, spectrally-resolved fluorescence microscopy measurements on single-cells revealed that this sensor molecule could also be used for imaging the cellular uptake of cyanide species from aq. solution contaminated with NaCN. Our results confirmed that statistical analysis of integrated intensity and transition energy obtained from the emission spectra collected over various microscopic sub-cellular regions can potentially be used to discriminate the effects of local cellular environments and that due to cyanide detection.